2014
DOI: 10.1145/2579281.2579292
|View full text |Cite
|
Sign up to set email alerts
|

Neural network based black box testing

Abstract: Black Box Testing is immensely important because the source code of a module is not always available. Enterprise Resource Planning systems are also tested using Black Box Testing wherein all the test cases are not equally important. The prioritization of these test cases would be helpful in case of premature termination of testing, due to lack of resources. This paper proposes a Neural Network based method to prioritize test cases. The paper also presents guidelines for prioritizing test cases. The technique h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Research has shown that it has the same nonlinear approximation ability as BPNN. Still, it is especially suitable for small and medium sample data modeling that does not obey the ordinary distribution law [20][21][22][41][42][43][44][45][46]. Due to PPR, the model of independent variable weight sum is equal to 1 for multiple independent variables with collaborative constraints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has shown that it has the same nonlinear approximation ability as BPNN. Still, it is especially suitable for small and medium sample data modeling that does not obey the ordinary distribution law [20][21][22][41][42][43][44][45][46]. Due to PPR, the model of independent variable weight sum is equal to 1 for multiple independent variables with collaborative constraints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Along with the above mentioned things, it is important to reveal maximum number of bugs. In order to achieve this, test data for black box suite have been prioritized using NN approach [7]. The work used module interaction diagram (MID) generator [5] in order to determine the flow in which, modules call each other.…”
Section: Introductionmentioning
confidence: 99%
“…It therefore becomes essential to prioritize the test cases on the basis of their importance. The policies, that would determine the importance of test cases, have already been dealt with in one of the earlier works [7]. The model of automated test case generation has also been presented in one of our earlier works [5].…”
mentioning
confidence: 99%